Anti-Chinese Incident in West Java in 1963 - Pangestu, Dimas Aldi; Kumalasari, Dyah; Aman, Aman (History Department, Semarang State University and Historian Society of Indonesia, 2021)
Abstract: The paper aims to study the anti-Chinese incident in West Java. The research used the historiography method from Kuntowijoyo with the steps including topic selection, heuristic, source criticism, interpretation, and historiography. Ever since Indonesia's independence, the relationship between Pribumi and Chinese people is in social and economic discrepancy as they were experiencing an economic crisis. The strays of PRRI/Permesta and DI/TII still hold their grudge within the tough situation. What comes after is the riot between March and May 1963 that put Chinese people as the main target. On March 27, 1963, a raid happened in Cirebon initiated by the Pribumi. They attack the shops and houses of the Chinese people. The riot spread to Bandung on May 10, 1963, started with a fistfight between Chinese and Pribumi students in Bandung Institute of Technology. A day after, another riot is happening in Sumedang. From May 14 until 16, 1963, a series of property assaults are carried out by youngsters, students, and citizens in Bogor and Tasikmalaya. In Garut, vandalism happened on May 17 and 18, 1963, when the shops, houses, and factories were assaulted. From May 18 until 19, 1963, another riot started in Sukabumi when the mob began attacking the merchandise, properties, food supply, and Sukabumi market. This Chinese attacking incident involving Pribumi youngsters, college and high school students, and citizens. The incident was originally planned to be carried out throughout cities in West Java, but it did not turn out well. The initiators are scattered in every part of the cities in West Java, mostly dominated by college and school students and some residents. The impact of this incident is the spike in commodity prices and further social discrepancy.Ã‚Â Abstrak: Artikel ini bertujuan mengkaji peristiwa anti Cina di Jawa Barat. Metode yang digunakan adalah metode sejarah Kuntowijoyo dengan langkah-langkah pemilihan topik, heuristik, kritik sumber, interpretasi dan historiografi. Sejak Indonesia merdeka hubungan Pribumi dan golongan Cina mempunyai kesenjangan hubungan sosial dengan ditambah keadaan krisis ekonomi. Sisa-sisa dari PRRI/Permesta dan DI/TII masih mempunyai reaksi ketidak puasan ditengah situasi yang sedang tidak menentukan. Akibatnya pada bulan Maret-Mei terjadi tindak kerusuhan yang merugikan golongan Cina. Pada tanggal 27 Maret 1963 pecah kerusuhan di Cirebon yang digerakan oleh kalangan Pribumi yang menyerang golongan Cina dengan merusak toko-toko dan rumah-rumah. Kerusuhan tersebut menjalar ke Bandung pada tanggal 10 Mei 1963 diawali oleh perkelahian di kampus ITB antara mahasiswa Cina dengan mahasiswa Pribumi. Pada 11 Mei 1963 pengrusakan kembali terjadi di Sumedang. Pada 14-16 Mei 1963 di Bogor dan Tasikmalaya terjadi pengrusakan yang dilakukan pemuda, pelajar dan rakyat. Di Garut aksi pengrusakan pecah pada 17-18 Mei 1963 dengan merusak rumah-rumah dan toko-toko serta pabrik-pabrik. Pada 18-19 Mei 1963 dimulai aksi di Sukabumi dengan merusak dagangan, perabotan rumah, persedian makanan dan pasar Sukabumi. Peristiwa kerusuhan yang terjadi merusak barang-barang golongan Cina yang dilakukan oleh mahasiswa, pelajar dan rakyat. Peristiwa tersebut sudah direncanakan diberbagai kota di Jawa Barat, namun tidak berjalan dengan baik. Dampak yang dirasakan adalah kenaikan harga barang dan kesenjangan sosial yang semakin parah.Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Cite this article: Pangestu, D.A., Kumalasari, D., Aman. (2021). Anti-Chinese Incident in West Java in 1963. Paramita: Historical Studies Journal,Ã‚Â 31(1), 93-103. http://dx.doi.org/10.15294/paramita.v31i1.23428Ã‚Â